Respuesta :

1) [tex] x^{2} +2x-10=0[/tex]
a=1
b=2
c=-10
[tex]x= \frac{-(2) +or- \sqrt{ 2^{2}+4(1)(-10) } }{2(1)} [/tex]
[tex]x= \frac{-2 + or - \sqrt{4+40} }{2} [/tex]
[tex]x= \frac{-2 +or- \sqrt{44} }{2} [/tex]
[tex]x= \frac{-2+or- 2\sqrt{11} }{2} [/tex]
[tex]x= -1+or- \sqrt{11} [/tex]
[tex] \sqrt{11}=3.32 [/tex]
-1+3.32 = 2.32
-1-3.32 = -4.32

2) 
[tex] x^{2} -2x-9=0 [/tex]
a=1
b=-2
c=-9
[tex]x= \frac{-(-2)+or- \sqrt{ (-2)^{2}+4(1)(-9) } }{2(1)} [/tex]
[tex]x= \frac{2+or- \sqrt{4+36} }{2} [/tex]
[tex]x= \frac{2+or- \sqrt{40} }{2} [/tex]
[tex]x= \frac{2+or-2 \sqrt{10} }{2} [/tex]
[tex]x=1+or- \sqrt{10} [/tex]
[tex] \sqrt{10} =3.16[/tex]
1+3.16 = 4.16
1-3.16 = -2.16

3) 
[tex] x^{2} -9x+5=0[/tex]
a=1
b=-9
c=5
[tex]x= \frac{-(-9)+or- \sqrt{(-9)^{2}-4(1)(5) } }{2} [/tex]
[tex]x= \frac{9+or- \sqrt{81-20} }{2} [/tex]
[tex]x= \frac{9+or- \sqrt{61} }{2} [/tex]
[tex]x= \frac{9}{2} +or- \frac{ \sqrt{61} }{2} [/tex]
[tex] \sqrt{61} = 7.81[/tex]
[tex] \frac{7.81}{2} =3.91[/tex]
[tex] \frac{9}{2}=4.5 [/tex]
4.5+3.91 = 8.41
4.5-3.91 = 0.59